The Use of Edmodo Application System to Increase Motivation for Learning English in the Second Semester of English Department at Madura Islamic University - Linta Wafdan Hidayah; Samsi Rijal; Rahmawati Ardila (Journal of Language, Literature and Teaching, 2019)
The use of technology in learning English is very important in today's modern era which is fully digital and electronic. Edmodo is one application of technology that can be used in the process of teaching and learning activities, also useful in learning English. Edmodo application can increase motivation to learn English and balance the development of an era that is completely sophisticated and fully uses electronic media technology. English learning in the second semester is the object of research and use of Edmodo system because second-semester students are considered to be still transitioning to emotional change so they need additional guidance in learning. The use of Edmodo is very useful for the second-semester students because they can discuss and share further online both with the lecturer and classmates. To support this research, researchers used descriptive qualitative. Edmodo is a developing application technology is very useful and important as a tool to assist lecturers in facilitating teaching and learning activities. This research focuses on the role of using Edmodo application in learning English to improve their learning skills and motivation of course. Keyword: Edmodo, application, improve, learning English